Pembuatan Taman Kita “Taman Dusun Sudimampir” Sebagai Objek Wisata (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
This community service research is about the creation of Taman Kita “Taman Dusun Sudimampir” as an artificial tourism to utilize local potential implemented in Kaliangsana Village, Kalijati District, Subang Regency. This artificial tourism destination is one of the incidental activity programs carried out by the Faculty of Engineering, Civil Engineering Study Program, University of Subang together with the community in Sudimampir Hamlet in an effort to increase environmental attractiveness while encouraging the economic growth of the local community. Sudimampir Hamlet is located in Kaliangsana Village and has beautiful and strategic natural conditions, but has not been optimally managed as a tourist destination. Therefore, it is necessary to develop an area in the form of a thematic park that can function as a means of recreation, education, and community empowerment. The method of implementation of this research activity includes the stages of planning, preparation, implementation, and management of the park. The concept of the park is educational and family-friendly nature tourism by providing various facilities such as flower gardens, children's play areas, photo spots, gazebos, and educational gardens. In addition, this park also involves active community participation in the management and development of micro-enterprises. The expected results of the development of this park are the creation of comfortable green open spaces, increased tourist visits, and the opening of new business opportunities for the surrounding community. Thus, Sudimampir Hamlet Park is expected to become a sustainable tourist attraction and provide social, economic, and environmental benefits.